Penerapan Metode Access Control List Pada Jaringan VLAN Menggunakan Router Cisco - Umar Hasan; sari dewi; Firmansyah (IMTechno: Journal of Industrial Management and Technology, 2022)
In the rapid development of information technology, the role of information technology is very important for a company that is especially engaged in technology. In companies engaged in technology solution services, optimizing information technology assets, management of hardware and software is the main thing. In addressing these problems, researchers will implement grouping and distribution of network access rights which aim to manage networking devices in the same broadcast. By using the Access Control List Routing method. VLAN technology is a virtual network to share the network in the same device in this case the settings on the Cisco router, so that it can communicate with different networks even though they are physically in the same segment. The Access Control List network provides a network security solution because of the blocking system for access outside the network that has been set up.